A High-Sensitive Detection of Several Tens of nM of Amyloid-Beta by Cantilever-Type Biosensor Immobilized DPPC Liposome Incorporated with Cholesterol. (2016) - Murakami, Y.; Zhang, Z.; Taniguchi, T.; Sohgawa, M.; Yamashita, K.; Noda, M.
Abstract: We have previously developed a NiCr strain-gauge cantilever-based biosensor with liposomes as sensing biomolecules immobilized on the cantilever surface to investigate time course of dynamic behaviour of amyloid-beta (1-40) protein on lipid membrane[1] . In this work, we attempt to improve effectively the sensitivity of the cantilever sensor by incorporating liposome with cholesterol to enhance Aβ-membrane interaction. Consequently, the sensitivity of the biosensor is significantly improved as 50-nM Aβ(1-40) has been detected. This result shows the possibility of detecting Aβ(1-40) in plasma of Alzheimer's disease (AD) patients because Aβ concentration in the plasma of AD patients is reported to be in the range from 75 to 100 nM[2] .